Spatial and temporal trends in the mortality burden of air pollution in China: 2004–2012. (January 2017) - Liu, Miaomiao; Huang, Yining; Ma, Zongwei; Jin, Zhou; Liu, Xingyu; Wang, Haikun; Liu, Yang; Wang, Jinnan; Jantunen, Matti; Bi, Jun; Kinney, Patrick L.
Abstract: While recent assessments have quantified the burden of air pollution at the national scale in China, air quality managers would benefit from assessments that disaggregate health impacts over regions and over time. We took advantage of a new 10 × 10 km satellite-based PM2.5 dataset to analyze spatial and temporal trends of air pollution health impacts in China, from 2004 to 2012. Results showed that national PM2.5 related deaths from stroke, ischemic heart disease and lung cancer increased from approximately 800, 000 cases in 2004 to over 1.2 million cases in 2012. The health burden exhibited strong spatial variations, with high attributable deaths concentrated in regions including the Beijing–Tianjin Metropolitan Region, Yangtze River Delta, Pearl River Delta, Sichuan Basin, Shandong, Wuhan Metropolitan Region, Changsha–Zhuzhou–Xiangtan, Henan, and Anhui, which have heavy air pollution, high population density, or both. Increasing trends were found in most provinces, but with varied growth rates. While there was some evidence for improving air quality in recent years, this was offset somewhat by the countervailing influences of in–migration together with population growth. We recommend that priority areas for future national air pollution control policies be adjusted to better reflect the spatial hotspots of health burdens. Satellite-based exposure and health impact assessments can be a useful tool for tracking progress on both air quality and population health burden reductions. Graphical abstract: Highlights: PM2.5 in China caused huge mortality burdens with increasing trends from 2004 to 2012. In–migration and population growth offset the health benefits of pollution control. Health burdens showed strong spatial variations within China. Adjust priority areas for pollution control to reflect the health-burden hotspots. This study adds useful spatial and temporal dimensions to prior estimates for China.